A sociodigital approach to investigating youth, teachers' and parents' experiences of smartphone banning in England - Coleman, Rebecca; Ringrose, Jessica (AoIR Selected Papers of Internet Research, 2026)
Smartphone bans or pledges signed by parents/carers to delay giving phones to young people are gaining international traction. Bans are usually based on arguments that smartphones are addictive, unhealthy and contribute to worsening educational outcomes. However, as a relatively new phenomenon, little existing research exists on the practical and experiential repercussions of these bans. Extant research shows that abstinence approaches to mitigating other potentially risky activities, including underage sex or drug and alcohol use, may increase harms, especially for vulnerable young people, and erode children’s rights. In this paper, we offer a preliminary analysis of our qualitative, multi-pronged study which seeks to better understand ‘on the ground’ experiences of the banning policies as they are rolled out in England. Working collaboratively with an educational charity, a media centre and a secondary school, our research explores the views of multiple actors and considers the varied contexts in which smartphone banning matters. We advance a sociodigital and postdigital approach, arguing that smartphones and people are engaged in complicated and processual human-media relations. We analyse the material and affective experiences of smartphone banning for young people, teachers and parents, exploring how banning smartphones doesn’t cut users off from digital mediation, but rather puts them in different relationships to these contexts. We offer some tentative recommendations for supportive structures in educational environments that are attentive to these sociodigital complexities, and which can help young people and adults navigate phone bans and the new relationalities around devices these set in play.